2014
DOI: 10.7763/ijesd.2014.v5.472
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Activated Carbon Derived from Rice Husk by Simple Carbonization and Chemical Activation for Using as Gasoline Adsorbent

Abstract: Abstract-Rice from Thailand is the top ranking of the world. The by-product of rice manufacturing is rice husk, which its usefulness is not fully attempt. The aims of research are to make value-added activated carbons of rice husk and to study the optimum conditions for gasoline adsorption using these activated carbons as adsorbents. All samples were analyzed for gasoline adsorption by gas chromatograph-mass spectrometry (GC-MS). The activated carbon of rice husk, which activated by H 3 PO 4 at temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…Implications for industrial applications AC adsorption proved to be successful for a wide range of pollutants (Tan et al 2008). Although the selected treatment methods in this study did not make a significant difference in the adsorption capacity of NO 3 À -N and PO 4 3À -P concentrations greater than 10 mg/L, these may be more needed and useful for the removal of other substances such as hydrocarbons (Cheenmatchaya & Kungwankunakorn 2014), metals (Low et al 1995;Annadurai et al 2002;Jain et al 2008) and other pollutants, such as dye (Al-Aoh et al 2013). Generally, when considering cost and environmental impacts, it is better to have fewer processes.…”
Section: Understanding Surface Characteristicsmentioning
confidence: 78%
See 1 more Smart Citation
“…Implications for industrial applications AC adsorption proved to be successful for a wide range of pollutants (Tan et al 2008). Although the selected treatment methods in this study did not make a significant difference in the adsorption capacity of NO 3 À -N and PO 4 3À -P concentrations greater than 10 mg/L, these may be more needed and useful for the removal of other substances such as hydrocarbons (Cheenmatchaya & Kungwankunakorn 2014), metals (Low et al 1995;Annadurai et al 2002;Jain et al 2008) and other pollutants, such as dye (Al-Aoh et al 2013). Generally, when considering cost and environmental impacts, it is better to have fewer processes.…”
Section: Understanding Surface Characteristicsmentioning
confidence: 78%
“…Using AC can be more affordable and environmentally friendly if sustainably sourced lignocellulosic agricultural waste is utilized (Cobb et al 2012). Lignocellulosic agricultural wastes such as bamboo (Hameed et al 2007), wood (Kilpimaa et al 2015), rice husks (Cheenmatchaya & Kungwankunakorn 2014), banana and orange peels (Annadurai et al 2002) and coconut shells (Gratuito et al 2008) have all been used to prepare AC. Kilpimaa et al (2015) demonstrated that AC derived from wood was suitable for phosphate and nitrate (PO 4 3À -P and NO 3 À -N, respectively) removal and had a higher adsorption capacity than commercially available AC.…”
Section: Introductionmentioning
confidence: 99%
“…They were used gas chromatograph-mass spectrometry for sample analysis for gasoline adsorption Authors were used phosphoric acid for activation at temperature of 450 °C, has the highest adsorption capacity. Physical characterization of the activated carbon obtained was performed by scanning electron microscopy [4]. Martha Ruiz et.al.Preparation Of Activated Carbon by Chemical Activation Using NaOH.…”
Section: Sukjit Kungwankunakorn Etal Preparation Of Activated Carbonmentioning
confidence: 99%
“…Lignocellulosic wastes are low-cost and renewable materials precursor for ACs production. ACs were prepared from numerous sources of biomass waste materials including coconut shell and husk, palm oil shells, cotton stalks, durian shell, rice husk, jackfruit peel and pomegranate seeds [6][7][8][9][10][11][12][13] etc. ACs preparation methods are classified as physical and chemical activation.…”
Section: Introductionmentioning
confidence: 99%